Apiáceas e alternarioses: tratamento de sementes, qualidade fisiológica e sanitária no armazenamento - Pedroso, Daniele Cardoso (2012)
Carrots, cilantro and parsley are vegetable, Apiaceae family, important in agriculture and Brazilian culinary. In recent years, the increasing production of these species led to the emergence of pest problems, especially diseases caused by fungi. In order to minimize the harmful effect of these fungi, the present study was to evaluate the effect of chemical and biological treatment, with or without polymer, in carrot coriander and parsley seeds, contaminated with A. alternata and A. radicina during storage. Were used seeds of carrot, coriander and parsley from producers in Rio Grande do Sul, without any chemical treatment, produced in 2009/2010. After receipt, the seeds were submitted to the initial assessment of water content, germination and health. According with the results of sanity test, in which was detected the presence of Alternaria alternata and A. radicina associated with seeds, were selected seeds of each species, according to the highest percentage of pathogens incidence. After, the seeds were submitted to treatment, according to manufacturers' recommendations, with fungicide Captan® (in dose of 0,002 g.kg-1) or with the biological product based on of Trichoderma spp., Agrotrich plus® (in dose of 25g.ha-1), both added or not polymer Collorseed - Rigran® (in dose of 50 mL. kg-1). Thus, the treatments were: control, seeds + Captan®, seed + Captan® + polymer, seeds + Agrotrich plus®, seeds + Agrotrich plus® + polymer. Quality assessments were performed every three months, the course of a year of storage. Physiological quality was evaluated by germination test, first count germination, cold test, seedling length, emergence and emergence rate index and the health quality through the Blotter test. The seeds treatment of carrot, coriander and parsley, contaminated with A. alternata and A. radicina with the fungicide Captan® + polymer favored the physiological and sanitary quality during storage. The Agrotrich plus®, polymer or not, did not show effectiveness in the treatment of the seed during storage. Additionally, the incidence of A. alternata and A. radicina reduced over twelve months of storage, regardless of the treatment applied to the apiaceas seed.